Exploring The Elements of Design - Evans, Poppy and Thomas, Mark (Australia Delmar Cengage Learning, 2008)
This volume presents the latest in graphic design concepts side-by-side with some of the best contemporary design work. This richly illustrated book offers explanations of the fundamental principles, examples of professional work, and diagrams that show how these principles operate in successful design solutions. Coverage begins with primary design elements, moves on to the use of color, typography, and imagery, and concludes with an overview of the field of graphic design and related career options. The authors include material on creative thinking, visual problem-solving, and research strategies used to pursue effective design solutions plus Web and New Media applications to reflect current media design trends.
Include Index, Glossary and Illustration
Keywords: Commercial art -- Graphic arts